65 Years on—Aflatoxin Biomarkers Blossoming: Whither Next? - Thomas W. Kensler; David L. Eaton (Toxins)
Aflatoxins are mycotoxins produced by Aspergillus flavus and several other related organisms and are common contaminants of numerous grains and nuts, especially maize (corn) and peanuts. Although, undoubtedly, aflatoxins have been present in the food of humans for millennia, their toxic effects were not discovered until 1960, first becoming evident as a non-infectious outbreak of poisoning of turkeys (Turkey X disease) arising from contaminated groundnut meal. The elucidation of specific chemical structures in 1963 led to the rapid characterization of aflatoxins as among the most potent chemical carcinogens of natural origin ever discovered. As a frontispiece to the Special Issue “65 Years on from Aflatoxin Discovery—A Themed Issue in Honor of Professor John D. Groopman”, we highlight many of Professor Groopman’s important contributions utilizing urinary (aflatoxin–N7–guanine) and, especially, serum (aflatoxin–albumin adducts) biomarkers; this work focused on over 40+ years of the development of analytical methods to measure biomarkers of aflatoxin exposure and their application in experimental and clinical studies. Collectively, this work serves as a template for using chemical-specific biomarkers as key tools to probe ‘exposure–disease relationships’—in this instance, dietary aflatoxins and liver cancer. New approaches to measuring carcinogen biomarkers will build upon this ‘aflatoxin paradigm’ to inform the public health implications of diverse exposures around the world.